Organizational Factors that Influence Implantation of Strategic Plans in Private Secondary Schools in Nairobi, Kenya - Nyagemi, Abel (University of Embu, 2017)
The study sought to find answers to the questions on implementation of strategic decision whereby it focused on private secondary schools in Nairobi County. Specifically, the study aimed at determining the effects of top management commitment, coordination of activities, employee skills and responsibilities and organization culture on implementation of strategic plans in private secondary schools in Nairobi County. A descriptive study was used since it was seen by the researcher as a more appropriate design for answering research questions which ask „how‟ and „why‟ and which do not require control over the events. The study population consisted of 119 staff of different cadres employed at various private secondary schools in Nairobi. Stratified sampling technique was used and out of 101 private secondary schools in Nairobi, 50 schools were randomly selected. In each of the selected schools, directors, principals or deputies, head of departments, teachers or support staff had an equal probability of being selected. The researcher administered a survey questionnaire individually to employees who were the target population. Data was analyzed using both inferential and descriptive statistics. Exploratory factor analysis was used in determining the influencing factors. The study established the following group of organizational factors as having an influence on implementation of strategic plans in private secondary schools in Nairobi: resource constraints, overlapping activities, interference from the local government, work pressure, conflict of interest, poor attitude, overlapping plans and tight timeframes. The conceptual model was tested and found to be having a statistically significant relationship among the implementation of strategic plans, top management commitment, coordination of activities, employee skills and responsibilities and organizational culture. The study recommends a further study on the specific factors should be done in particular sub-counties in large cities such as Mombasa to explain on how those factors affect implementation of strategic management plans in private schools at the sub county level.